Duolingo’s Impacts in Senior High Classrooms - Ramadani, Gladis Alifi; Andanty , Ferra Dian (Universitas Islam Negeri Palopo, 2025)
This study investigated the impact of using the Duolingo application on senior high school students' grammar achievement. A total of 70 students participated in the research, divided into experimental and control groups, to evaluate whether integrating Duolingo into language learning enhanced students' grammatical skills. The experimental group used Duolingo for grammar practice, while the control group followed traditional teaching methods. Pre-test and post-test scores were analysed to measure progress. The results indicated a significant improvement in the grammar scores of the experimental group, with an average increase from 66.14 (pre-test) to 76.57 (post-test). In contrast, the control group exhibited minimal improvement, maintaining an average score of 66.14. The findings suggested that Duolingo’s interactive and gamified features motivated students and enhanced their comprehension of grammar rules, leading to better performance. Statistical analysis confirmed that the difference in improvement was significant, leading to the acceptance of the alternative hypothesis (Ha) and the rejection of the null hypothesis (H0). This study underscored the potential of technology-based learning tools like Duolingo in promoting grammar proficiency among senior high school students. However, limitations regarding sample diversity and the duration of intervention highlighted the need for further research to validate long-term effectiveness.